Effect of Silicon Carbide on the Properties of Natural Rubber Blends with EPDM Rubber - Anancharoenwong, Ekasit; Marthosa, Sutida; Suklueng, Montri; Niyomwas, Sutham; Chaiprapat, Sumate (International Journal of Integrated Engineering, 2020)
Blends of natural rubber/ ethylene propylene diene monomer were prepared in an internal mixer. The semi-EV of sulphur was used. The effect of the silicon carbide (SiC) level (5, 10, 15, and 20 phr) on the cure characteristic, mechanical, thermal and morphology properties of silicon carbide ï¬lled 30:70 NR/EPDM were studied. The curing properties show that the tc90 and tS2 of NR/EPDM blends increased with the increasing SiC loading. The effect of SiC loading on the tensile strength of NR/EPDM blends showed that tensile of vulcanizates increased with the increasing SiC up until 10 phr, extra addition of SiC would deteriorate the tensile properties. The thermal oxidative property of SiC filled NR/EPDM were satisfactory at all SiC loadings.